Pengaruh Literasi Keuangan dan Pengetahuan akuntansi terhadap Perilaku Pengelolaan Keuangan Generasi Milenial - Sri Anawati; Noviyanti Noviyanti; Agnemas Yusoep Islami; Nur Fitri Dewi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study investigates how accounting and financial knowledge impacts how millennials manage their finances. A person’s ability to understand and control their finances, such as creating a budget, controlling expenses, managing savings, and investing, is called financial literacy. However, accounting expertise involves a deep understanding of financial concepts, fundamentals, and recording methods necessary for effective financial decision-making. The ability of millennials, consisting of individuals born between 1981 and 1996, to adapt to technology is well-known. Their consumptive lifestyle and lack of long-term financial planning also often put this group at risk. They are interesting to study in key areas such as education, career, and financial planning. To achieve this goal, the study used a questionnaire to collect primary data. This study is quantitative and conducted through a survey. To select respondents from millennials living in the Pondok Gede area, a purposive sampling method was used. The instrument used was a five-point Likert-scale questionnaire. The objective was to measure respondents’ knowledge and behavior regarding financial management and accounting. Furthermore, the collected data were analyzed using multiple linear regression to determine the simultaneous and partial effects of the two independent variables on the dependent variable. This study shows that knowledge of finance and accounting has a positive and significant impact on individual financial habits. Both factors also showed significant results separately, indicating a correlation between better accounting knowledge and better financial management practices. These results indicate that a better understanding of accounting and finance is crucial. These results highlight the importance of improving financial and accounting knowledge through formal education, training, and the use of digital media to develop healthy financial behaviors.